Seasonal and Diurnal Variations of Lightning Activity Over West Sumatra and Its Correlation with Precipitation Type - Saufina, Elfira; Marzuki, Marzuki; Vonnisa, Mutya; Hashiguchi, Hiroyuki; Harmadi, Harmadi (UI Scholars Hub, 2018)
Seasonal and diurnal variations of lightning activity over West Sumatra have been investigated using observations of Tropical Rainfall Measuring Mission–Lightning Imaging Sensor (TRMM–LIS) over a 16-year period. This study also used TRMM 3B43 and 2A25 data to observe the correlation between lightning activity with rainfall and precipitation type. Results show that lightning occurs more frequently over land than over ocean and coastal areas, in contrast to total rainfall, which is higher over ocean and coastalareas. The lightning pattern is similar to the convective rainfall (particularly deep convective) pattern, which indicates that the majority of lightning in West Sumatra is associated with deep convective rain. The lightning intensity in Indonesia during the convection period, namely, December–January–February and September–October–November, is higher than that during other periods. The diurnal cycle of lightning coincides with the diurnal cycle of cloud migration from the ocean to in land Sumatra, as reported in previous research. Lightning and deep convective precipitation are dominant during the day and evening (16.00–20.00 Local Standard Time [LST]), particularly over land. Stratiform precipitation occursmore frequentlyfrom afternoon to early morning (16.00–04.00 LST) over landand at 00.00–12.00 LST over the ocean.